An invitation to social theory - Inglis, David; Thorpe, Christopher (Polity Press, 2012)
* Wide-ranging introduction to social theory that carefully avoids simplification of ideas whilst presenting theories in an accessible language for students. * Inspired by the authors' own teaching and dissatisfaction with current books on the market to provide accessible yet sophisticated guides to social theory